Predicting HBsAg clearance in genotype A chronic hepatitis B using HBsAg epitope profiling: A biomarker for functional cure. (21st August 2019) - Walsh, Renae; Hammond, Rachel; Yuen, Lilly; Deerain, Joshua; O'Donnell, Tanya; Leary, Thomas; Cloherty, Gavin; Gaggar, Anuj; Kitrinos, Kathryn; Subramanian, Mani; Wong, Darren; Locarnini, Stephen
Abstract: Background and Aim: Functional cure is the major goal of chronic hepatitis B (CHB) therapy though few biomarkers predict this outcome. HBsAg epitope occupancy can be influenced by therapeutic and immune pressure. The aim of this study was to map the HBsAg epitope profiles during long‐term nucleos(t)ide analogue therapy in patients with genotype A CHB, in the context of HBsAg loss (SL)/seroconversion. Methods: We evaluated 25 genotype A CHB patients in the GS‐US‐174‐0103 trial of HBeAg‐positive CHB patients treated with tenofovir or adefovir for 4 years, 14 who achieved SL whilst 11 had no change. We epitope mapped the major domains of HBsAg to identify those patients with HBsAg clearance profile (CP) (loss of binding at both loops 1 and 2 epitopes of the 'a' determinant) vs non‐clearance profile (no change in epitope recognition, or loss of epitope binding at one loop only), correlating this to on‐treatment HBsAg responses. Complexed anti‐HBs was also measured. Results: Analysis of the HBsAg epitope profiles of the 25 patients at baseline identified no predictive correlation with SL. In contrast, analysis at week 48 and end of study (week 192) or prior to SL identified significant predictive associations between development of HBsAg CPs and outcome of functional cure. The detection of a CP also correlated with the development of an alanine aminotransferase flare and detection of anti‐HBs complexed with HBsAg. Conclusion: The detection of HBsAg CPs by epitope mapping represents a novel viral biomarker, reflecting an emerging anti‐HBs selection pressure prior to functional cure.